Cognitive Reflection in Project Competencies: Questions of Planning Socio-Pedagogical Support of Students in the University Environment (Journal of Educational Sciences, 2019)
The researchers with the quality of reflection of students in the planning system of socio-pedagogical support of the formation of their project competence. The study was conducted to determine the pedagogical actions necessary to help students to understand the emerging professional and career situation based on the reflection of what is happening. The author’s leading idea is to design a system of socio-pedagogical support for the formation of students ‘ project competence based on the data of diagnostics of the quality of their cognitive-reflective activity and the organization of the development of the theoretical model of maneuvering between the predicted and spontaneous possibilities in the design of life strategy. The researchers clarify the concepts of «cognitive reflection», «theoretical model of maneuvering between predicted and spontaneous opportunities in the design of life strategy»; created and tested a technique for diagnosing the quality of cognitive reflection of students of personal situations in the process of acquiring a profession. In the practical part of the work, the authors propose a system of necessary pedagogical actions to help students understand the emerging life situation on the basis of reflection of what is happening to choose an effective professional career strategy. The study involved 140 students majoring 5B012300-Social pedagogy and self-cognition (73 students of al-Farabi KazNU and 67 students of Abay KazNPU). Key words: social and pedagogical support, project competence, educational and professional activity, autobiographical knowledge, cognitive reflection